2016
DOI: 10.18805/lr.v0iof.9290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trap design and weather factors on relative efficiency of yellow sticky traps for sampling aphids in groundnut

Abstract: The present investigations were carried to evaluate the trapping efficiency of three different yellow sticky traps for monitoring of aphid population in groundnut with relation to weather factors. The aphid population was found comparatively higher during January to March every year. The number of aphid (alates) caught was significantly higher on inverted dust bin traps followed by round plate traps and rectangular tray trap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Four sampling techniques were studied: leaf beating on a white plastic tray (LBPT) (35‐cm length × 30‐cm width × 5‐cm depth), direct counting (DC) of insects on both leaf surfaces (abaxial and adaxial), whole leaf collection in paper bags (WLCPB) and yellow stick trap (YST). These techniques were chosen because they are the most frequently used techniques for sampling sap‐feeding insects (Jasrotia, Nataraja, Harish, Dutta, & Savaliya, ; Moura et al, ; Pinto et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four sampling techniques were studied: leaf beating on a white plastic tray (LBPT) (35‐cm length × 30‐cm width × 5‐cm depth), direct counting (DC) of insects on both leaf surfaces (abaxial and adaxial), whole leaf collection in paper bags (WLCPB) and yellow stick trap (YST). These techniques were chosen because they are the most frequently used techniques for sampling sap‐feeding insects (Jasrotia, Nataraja, Harish, Dutta, & Savaliya, ; Moura et al, ; Pinto et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These techniques were chosen because they are the most frequently used techniques for sampling sap-feeding insects (Jasrotia, Nataraja, Harish, Dutta, & Savaliya, 2016;Moura et al, 2007;Pinto et al, 2017).…”
Section: Selection Of the Best Technique For Sampling Aphis Gossypimentioning
confidence: 99%
“…Contrary to Karnal, trap type was the main factor and alone contributed 17.8 and 45.5 %, respectively whereas trap height contributed least towards the trap efficiency at Niphad location. Backward stepwise regression modelling indicated that Döring, 2014;Jasrotia et al, 2016;Perring et al, 2018;Holland et al, 2019). The possible reason for greater attraction to yellow colour is associated with young, senescing or infected foliage that tends to indicate higher availability of nutrients such as aminoacids (Hodge and Powell, 2010;Farnier et al, 2014).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, the efficiency level is dependent on their color, which can differ for different pests. For example, for whiteflies and aphids yellow sticky board is effective, whereas for thrips species blue is reliably effective (Jasrotia et al 2016). The number of onion thrips from sticky boards and plant samples should be counted in the laboratory.…”
Section: Monitoring and Treatment Decisions With Regard To Onion Thrimentioning
confidence: 99%